Drawn to work: what makes apprenticeship training an attractive choice for the working-class - Altreiter, Carina [Verfasser] (My University, 2021)
“The article investigates mechanisms of class reproduction by looking at school-to-work transitions of young blue-collar workers from Austria. The study adopts a Bourdieusian explanatory framework to show how working-class kids are guided towards picking up apprenticeship training instead of pursuing further education. Two classed dispositions are presented as a crucial influence: first, a preference for practical and manual labour. Second, the embodiment of wage labour not only as an economic necessity but as a foundation for recognition and appreciation. The results point to the importance of analysing educational decision-making not only in the context of the educational system but also with regard to the labour market and the different values and meanings attached to both spheres.” (author’s abstract)
Keywords: G 1.3.2.2 Übergänge; L 5 Beratung & Orientierung; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; 370; 300; Jugendlicher; Arbeiterklasse; Berufseinmündung; Bildungsentscheidung; Erste Schwelle; Einflussfaktor; Manuelle Arbeit; Körperliche Arbeit; Lohn; Wertschätzung; Österreich